2007
DOI: 10.1007/bf03346311
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year follow-up of thyroid function in lithium patients

Abstract: Lithium may be associated with hypothyroidism in particular in the presence of circulating thyroid antibodies. Incidence of thyroid antibodies is comparable with that reported for the general population. Hyperthyroidism and thyroid cancer are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 19 publications
4
48
0
Order By: Relevance
“…31 In a 15-year follow-up study of Bocchetta et al, yearly hypothyroidism ratio was found at 1.5% in lithium-treated bipolar patients. 32 No patients devel- Under the light of our findings, it may be suggested that lithium treatment is safe in patients who stayed euthyroid when using lithium and treatment may be continued by doing required tests. Increased thyroid volume on ultrasonography is an expected finding in patients who have been using lithium for a long time.…”
Section: Discussionmentioning
confidence: 70%
“…31 In a 15-year follow-up study of Bocchetta et al, yearly hypothyroidism ratio was found at 1.5% in lithium-treated bipolar patients. 32 No patients devel- Under the light of our findings, it may be suggested that lithium treatment is safe in patients who stayed euthyroid when using lithium and treatment may be continued by doing required tests. Increased thyroid volume on ultrasonography is an expected finding in patients who have been using lithium for a long time.…”
Section: Discussionmentioning
confidence: 70%
“…Figure 1 presents the clinical comorbidities exhibited by studied patients, where the most commonly observed ones were: hypertension (50%), obesity (46.4%), hypothyroidism (39.3%), and gastric problems (32.1%). It is known that bipolar patients are more susceptible to clinical comorbidities (Angst et al, 2000) and many of these could be due to utilized medications, such as hypothyroidism (Bocchetta et al, 2007) and obesity (Ketter, Haupt, 2006;Garcia-Portilla et al, 2008). It is also known that lithium and valproate could lead to hypothyroidism, and that mood stabilizers and antipsychotics could lead to obesity.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of newer thyroid antibodies is more in a state of long term lithium intake because it augments the activity of B lymphocytes and reducing the ratio of circulating suppressor to cytotoxic T cells. The presence of thyroid antibody in lithium induced hypothyroidism requires supplementation of thyroxine [3,4]. Other risk factors for lithium induced hypothyroidism are older age, longer duration of drug intake, female sex, and co-existing iodine deficiency [5].…”
Section: Parametersmentioning
confidence: 99%